Chemical Characterization of Archaeological Pulp Stones from 18th–19th Century Radom, Poland: A Pilot Study - Jacek Tomczyk; Piotr Regulski; Katarzyna Góralczyk; Grzegorz Tylko (Anthropological Review, 2025)
The purpose of this study was to evaluate the calcium (Ca) and phosphorus (P) contents of pulp stones in a historical population (18th–19th centuries) from Radom, Poland. Ten molars from adults from the Radom cemetery (18th–19th centuries) were used in the study. The crowns of the teeth were mechanically opened, and visible pulp stones were examined with a scanning electron microscope equipped with a Si(Li) energy dispersive detector (energy dispersive X-ray spectrometry detector, which uses a lithium (Li)- doped silicon (Si) single-crystal semiconductor as a detector element). Enamel presented higher values of Ca/P ratio compared with the dentine and/or pulp stones. Moreover, in one case, the external layer of the pulp stone had significantly lower Ca and P contents compared with the internal layer (Ca: 13.97±0.31 vs. 34.2±0.37 [wt%]; P: 6.13±0.21 vs. 16.5±0.34 [wt%]). Evaluation of the Ca and P composition of the analyzed enamel and dentine in the Radom samples from the 18th–19th centuries produced findings that are consistent with studies conducted on teeth from contemporary populations. In the case of one individual, two chemically distinct layers were diagnosed in the pulp stone. It is difficult to interpret this finding based on a single case, but it may be due to the fact that the outer layer is characterized by higher organic structure.